Selective dual-band metamaterial perfect absorber for infrared stealth technology - Jagyeong Kim (Nature Portfolio, 2017)
Abstract We propose a dual-band metamaterial perfect absorber with a metal–insulator–metal structure (MIM) for use in infrared (IR) stealth technology. We designed the MIM structure to have surface plasmon polariton (SPP) and magnetic polariton (MP) resonance peaks at 1.54 μm and 6.2 μm, respectively. One peak suppresses the scattering signals used by laser-guided missiles, and the other matches the atmospheric absorption band, thereby enabling the suppression of long-wavelength IR (LWIR) and mid-wavelength IR (MWIR) signals from objects as they propagate through the air. We analysed the spectral properties of the resonance peaks by comparing the wavelength of the MP peak calculated using the finite-difference time-domain method with that obtained by utilizing an inductor–capacitor circuit model. We evaluated the dependence of the performance of the dual-band metamaterial perfect absorber on the incident angle of light at the surface. The proposed absorber was able to reduce the scattering of 1.54 μm IR laser light by more than 90% and suppress the MWIR and LWIR signatures by more than 92%, as well as maintain MWIR and LWIR signal reduction rates greater than 90% across a wide temperature range from room temperature to 500 °C.